(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The dramatic growth in Indian elementary educationenrollment and improvements in retention and transition rates over the past tenyears, particularly among more disadvantaged groups, are increasing pressure onthe secondary level to absorb new entrants. Given ongoing center and stateinvestments in Sarva Shiksha Abhiyan (Education for All), this trend willcontinue for the next 10 years. At the same time, India’s impressive, sustainedeconomic growth has increased household and labor market demand for secondaryand higher education. Secondary education’s contribution to economic growth,demonstrated high social benefits (particularly for girls), and support ofdemocratic citizenship reinforce the need for increased public support at thislevel, particularly in light of the very large inequalities in access tosecondary education, by income, gender, social group and geography. The challenge is to dramatically improve access, equityand quality of secondary education simultaneously. Government has an importantrole to play in improving equity of secondary education. The bulk of the growthin secondary education over the last ten years has been financed by householdsfor private schooling, such that the typical secondary school student is male,urban and middle class. Whether because of poverty, credit constraints, lack ofinformation about perceived benefits of schooling, cultural norms or otherfactors, access to secondary education by girls and by children from scheduledcastes, scheduled tribes, rural and poor households is significantly lower thanstate and national averages. Indicators of internal efficiency and quality oflearning among these groups are also well below average. Targeted, supply- anddemandside programs for these groups are called for. The recently launched centrally sponsored scheme forsecondary education, Rashtriya Madhyamik Shiksha Abhiyan (RMSA), offers astrategic opportunity to improve access and equity; enhance quality,accountability and ability to measure learning outcomes; and promotestandardization of curriculum and examinations across states. In addition,India’s recent decision to participate in international assessments of studentachievement is an extremely positive sign. Over time, such participation willprovide an important objective baseline of students’ cognitive skills and afuture measure of success of the country’s investments in elementary andsecondary education.